PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS MODEL DISCOVERY LEARNING PADA MATERI BARISAN DAN DERET - Takwa, Takwa; Mania, Sitti; Abrar, Andi Ika Prasasti; Nur, Fitriani; Mattoliang, Lisnasari Andi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
This study aims to develop mathematics teaching materials based on discovery learning models on the subject of sequences and series. This type of research is Research & Development (R&D). The development model used is the model proposed by Plomp which consists of the initial investigation phase, the design phase, the realization phase and the evaluation and revision test phases. The test subjects in this study were students of class XI MAN 1 Makassar. The instruments used in this study were the expert validation sheet, the observation sheet of the teacher's ability to manage learning, the student activity observation sheet, the student response questionnaire, the teacher response questionnaire and the conceptual understanding test. Based on the results of the trials conducted, it was found that the teaching materials developed met the valid, practical, and effective criteria.